In Vivo Genome-Wide PGR Binding in Pregnant Human Myometrium Identifies Potential Regulators of Labor - Dotts, Ariel J.; Reiman, Derek; Yin, Ping; Kujawa, Stacy; Grobman, William A.; Dai, Yang; Bulun, Serdar E. (Reproductive sciences (Thousand Oaks, Calif.), 2023)
The alterations in myometrial biology during labor are not well understood. The myometrium is the contractile portion of the uterus and contributes to labor, a process that may be regulated by the steroid hormone progesterone. Thus, human myometrial tissues from term pregnant in-active-labor (TIL) and term pregnant not-in-labor (TNIL) subjects were used for genome-wide analyses to elucidate potential future preventive or therapeutic targets involved in the regulation of labor. Using myometrial tissues directly subjected to RNA sequencing (RNA-seq), progesterone receptor (PGR) chromatin immunoprecipitation sequencing (ChIP-seq), and histone modification ChIP-seq, we profiled genome-wide changes associated with gene expression in myometrial smooth muscle tissue in vivo. In TIL myometrium, PGR predominantly occupied promoter regions, including the classical progesterone response element, whereas it bound mainly to intergenic regions in TNIL myometrial tissue. Differential binding analysis uncovered over 1700 differential PGR-bound sites between TIL and TNIL, with 1361 sites gained and 428 lost in labor. Functional analysis identified multiple pathways involved in cAMP-mediated signaling enriched in labor. A three-way integration of the data for ChIP-seq, RNA-seq, and active histone marks uncovered the following genes associated with PGR binding, transcriptional activation, and altered mRNA levels: ATP11A, CBX7, and TNS1. In vitro studies showed that ATP11A, CBX7, and TNS1 are progesterone responsive. We speculate that these genes may contribute to the contractile phenotype of the myometrium during various stages of labor. In conclusion, we provide novel labor-associated genome-wide events and PGR-target genes that can serve as targets for future mechanistic studies.